Didactic Potential of Modern Information Technologies in Training a Chemistry Graduate - Elena V.; Mikhail A.; Roman V.; Larisa V.; Mark M. (National Research Mordova State University, 2018)
Introduction: the article deals with maintaining the quality of teaching during curtailment of academic hours in curriculum. A university teacher should motivate students to use modern information technology training. The authors of the article describe the optimal didactic capabilities of modern information technologies to be used to improve the preparedness of a chemistry graduate. The aim of the article is to highlight the problem of finding the optimal didactic capabilities of modern information technologies used for improving the system of training specialists in the field of chemistry and to discuss the results of current studies in this direction. Materials and Methods: the authors summarised the relevant literature and results of the research and teaching experience. The main theoretical methods of research are modeling and designing the process of incorporating modern information technologies into the teaching of chemistry in the university. Theoretical methods are supplemented by empirical methods, such as observation, survey, testing, experimental work and methodological analysis. Results: the article reveals the main components of the system of teaching chemistry at higher educational establishments using information technology, identifies necessary electronic didactic materials for their implementation, training and monitoring programmes, presents their approbation in real conditions of pedagogical activity and the results obtained. The article presents the results of a pedagogical experiment, which proves the effectiveness of using these approaches in the training of chemists. Discussion and Conclusions: the electronic educational materials, manuals and recommendations developed by the authors can be used in teachinga future chemistry graduate in a number of chemical disciplines and can serve as a basis for the development of information, communication and instrumental provision in other chemical subjects. The main directions for further research are as follows: to create and to test electronic textbooks and teaching aids, to develop variants of using Internet technologies in teaching chemistry.